Guidance for professional development in drinking water and wastewater industry - Ambulkar, Archis (IWA Publishing, 2015)
Guidance for Professional Development in Drinking Water and Wastewater Industryis useful for every professional in the industry and particularly prospective students. It can be used by mentors and established practitioners as a guidance tool for training newcomers.